Az elítélt alapjogainak megjelenése a büntetés-végrehajtásban - Véger Alexandra (A Pázmány Péter Katolikus Egyetem Jog- és Államtudományi Karának Könyvei. Doktorandusz Tanulmányok, 2020)
The main thrust of my research is the emergence and enforcement of the right of redress for detainees in the penitentiary complaint mechanism against violations. My present study touches on the part of my research to deduce that detainees have fundamental rights that cannot be alienated from him despite serving any length of sentence, and to point out why the present purpose of sentencing is reintegration. I have tried to clash as many approaches as possible that still raise serious philosophical questions to this day. Primarily, conceptually and substantively, I tried to seize the right to today’s restorative justice to meet social, criminal policy, European Community and international expectations, to meet needs and to strike a balance between needs and expectations, which is often beyond the legislature, legislators and legislators. depends on their specifi c discretion and criminal treatment. At the same time, in my present outlook, I have summarized all the universal documents that were the fi rst to embrace and fi ght for the fundamental rights of detainees.